COVID-19 and trauma: how social distancing orders altered the patient population using trauma services during the 2020 pandemic. Issue 1 (17th February 2021) - Pelzl, Casey E; Salottolo, Kristin; Banton, Kaysie; Madayag, Robert M; Hamilton, David; Duane, Therese M; Carrick, Matthew; Lieser, Mark; Berg, Gina; Bar-Or, David
Abstract : Background: Recent studies have reported changes in trauma volumes resulting from the COVID-19 pandemic and social distancing orders (SDOs) implemented by federal and state governments. However, literature is lacking on demographic, injury and outcome patterns. Methods: This retrospective, cross-sectional study included patients aged ≥18 years at six US level 1 trauma centers. Patients not discharged by the date of data acquisition were excluded. Demographic, injury and outcome variables were assessed across four time periods: period 1 (January 1, 2019–December 31, 2019); period 1b (March 16, 2019–June 30, 2019); period 2 (January 1, 2020–March 15, 2020); and period 3 (March 16, 2020–June 30, 2020). Patients admitted in period 3 were compared with patients presenting during all other periods. Categorical data were compared with χ 2 and Fisher's exact tests, and continuous data were assessed with Student's t-tests and Wilcoxon rank-sum tests. Results: We identified 18 567 patients: 12 797 patients in period 1 (including 3707 in period 1b), 2488 in period 2 and 3282 in period 3. Compared with period 1, period 3 had a statistically significant decrease in mean patient volume, increase in portion of penetrating injuries, increase in higher levels of trauma activation, change in emergency department discharge disposition locations, increase in in-hospital mortality and a shorter hospital length of stay. Comparison between period 1b and period 3 demonstrated a decrease in mean patient volume, increase in penetrating injuries, increase in high acuity trauma activations and increase in in-hospital mortality rate. From period 2 to period 3, the penetrating injuries rose from 6.7% to 9.4% (p=0.004), injury severity scale ≥25 increased from 5.9% to 7.7% (p=0.002), full trauma team activations increased from 13.7% to 16.4% (p<0.001), interhospital transfers decreased from 36.7% to 31.6% (p<0.001) and the in-hospital mortality rate increased from 3.3% to 4.2% (p=0.003). Discussion: Beyond altering social interactions among people, the federal SDO is associated with changes in trauma volumes, demographics and injury patterns among patients seeking care at six level 1 hospitals during the pandemic. Level of evidence: IV, prognostic and epidemiological.